Biosorption of Neodymium by Selected Photoautotrophic and Heterotrophic Species - Heilmann, Marcus; Jurkowski, Wojciech; Buchholz, Rainer; Brueck, Thomas; Becker, Anna (Journal of Chemical Engineering & Process Technology, 2015)
In a search for alternative methods for isolation of rare earth elements from diluted solutions, a possibility of their preconcentration on biomass of mainly phototrophic species, that can be easily cultivated in open or closed systems, was investigated in this study. A screening of 19 biological species, consisting of 17 microalgae, one yeast and one moss, in regard to the biosorption of neodymium (Nd) on their lyophilized biomass was performed. Maximum sorption capacity (qm) was determined after incubation for 3 h at room temperature and centrifugation through measuring the Nd content in the supernatant via a spectrophotometric assay. The obtained qm values ranged from 0.26 mmol*g-1 for Chlamydomonas reinhardtii to 0.48 mmol*g-1 for Calothrix brevissima and up to 0.74 mmol*g-1 for Physcomitrella patens. Kinetic measurements show the reaching of qm after 30 min for C. reinhardtii and 180 min for P. patens. Based on titration studies the proton exchange capacity was found to be 0.39 mmol*g-1 for C. reinhardtii and 0.44 mmol*g-1 for P. patens leading to a conclusion that proton exchange was mainly responsible for the biosorption mechanism. To our knowledge it is the first report of screening regarding such a wide scope of microalgae for a sorption of Nd. <
UnivIS-Import:2018-09-05:Pub.2015.tech.ITC.cbiove.biosor
Keywords: biosorption; microalgae; lyophilized biomass; recovery of Nd from highly diluted solutions; mechanism